Sweet Thursday [compact disc, unabridged] - Steinbeck, John, 1902-1968 (Penguin classics., 2011)
In Monterey, on the California coast, Sweet Thursday is what they call the day after Lousy Wednesday, which is one of those days that are just naturally bad. John Steinbeck once more brings to life the denizens of a netherworld of laughter and tears from Fauna, new headmistress of the local brothel, to Hazel, a bum whose mother must have wanted a daughter.